A Legal Analysis Of The Bell Of Jaffna Fortress As A Colonial Cultural Property: Prospects And Challenges For Sri Lanka - Madhushan, G.P.D. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
Culture is a significant and magnificent element of any society which is a collective effort of the process of human civilization. The objects/property attached to such cultures reflect the richness of human innovations, interactions and engagement of their daily routines. The Bell of Jaffna Fortress, with the VOC monogram and dated 1747, is likely to have been the bell of the belfry inside the fort or above the gate, used to call people to work, or to sound the alarm. Provenance research discovers that Captain James Stewart (1784-1843), who died in Colombo, possibly took the bell from the fortress and sent it to the family estate in Scotland. The bell remained in Stenton House Garden until the house was sold at the end of 2019. Therefore, the background of this bell undoubtedly demonstrates the importance of cultural value of Sri Lanka though it is currently outside its country of origin, leaving important unanswered legal implications to address. First, the legality of acquiring this bell is crucial since it occurred during the period of European colonization in Sri Lanka with a heavy power imbalance between the colonizer and the colony. Second, the current ownership of the bell is with a private art dealer and not with a State Museum of Netherlands. This makes more ambiguous the process of repatriation of the bell which is outside the preview of the Dutch Restitution Policy. Though UNESCO and UNIDROIT conventions cover the protection of cultural property in general, there is a self-barrier in terms of colonial cultural property which do not have retroactive effect. Therefore, this research investigates the legality of acquiring the Bell of Jaffna fortress as a colonial cultural property and its legal implications of repatriation which is unaddressed in the Dutch Restitution Policy specific to the objects/property under the ownership or possession of private domain/collections. This research employs doctrinal method of inquiry and Desk-based investigations as the primary method of data collection.
Keywords: Colonial cultural property; Legality; Dutch restitution policy; Restitution; Private collections